2014
DOI: 10.1093/abbs/gmu038
|View full text |Cite
|
Sign up to set email alerts
|

Global identification of CobB interactors by an <italic>Escherichia coli</italic> proteome microarray

Abstract: Protein acetylation is one of the most abundant posttranslational modifications and plays critical roles in many important biological processes. Based on the recent advances in mass spectrometry technology, in bacteria, such as Escherichia coli, tremendous acetylated proteins and acetylation sites have been identified. However, only one protein deacetylase, i.e. CobB, has been identified in E. coli so far. How CobB is regulated is still elusive. One right strategy to study the regulation of CobB is to globally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
(35 reference statements)
2
19
0
Order By: Relevance
“…When >60% of full length proteins encoded by a given organism are presented on a functional protein array, they can be referred as proteome arrays. To this date, proteome arrays have been constructed for several important model organisms, such as Escherichia coli [16], Saccharomyces cerevisiae [17], and humans [3], [18]. In recent years, proteins over-expressed in tissue culture or in vitro translated without further purification have also been used to fabricate functional protein arrays [19], [20].…”
Section: Overview Of the Protein Array Technologymentioning
confidence: 99%
“…When >60% of full length proteins encoded by a given organism are presented on a functional protein array, they can be referred as proteome arrays. To this date, proteome arrays have been constructed for several important model organisms, such as Escherichia coli [16], Saccharomyces cerevisiae [17], and humans [3], [18]. In recent years, proteins over-expressed in tissue culture or in vitro translated without further purification have also been used to fabricate functional protein arrays [19], [20].…”
Section: Overview Of the Protein Array Technologymentioning
confidence: 99%
“…In contrast, functional protein microarray usually covers a huge amount of proteins on a single slide [29], sometimes near the total proteome of an organism, for example Escherichia coli [30,31], Saccharomyces cerevisiae [18,32], and humans [33]. In general, the immobilized proteins on functional protein microarray are expressed in engineered bacteria or yeast and most of them are not well characterized.…”
Section: Protein Microarrays and Their Fabricationmentioning
confidence: 99%
“…TopA has been demonstrated in a previous study to be a CobB binding protein using a proteome microarray as well as bio-layer interferometry analysis (Liu et at.,2014). Purified recombinant TopA and His-tagged CobB were allowed to interact before pull-down by HisPur Cobalt Agarose Resin.…”
Section: Topa Interacts Directly With Cobb In the Absence Of Dnamentioning
confidence: 99%
“…Proteomics studies have revealed multiple lysine sites on E. coli topoisomerase I as targets of lysine acetylation (Yu et al, 2008;Zhang et al, 2009a). Moreover, the proteome microarray assay identified a strong interaction between a deacetylase and E. coli topoisomerase I suggesting the importance of regulation of lysine acetylation in E. coli topoisomerase I (Liu et al, 2014). Similarly, eukaryotic topoisomerases have been found to be post-translationally modified by acetylation (Choudhary et al, 2009), phosphorylation (Wells et al, 1994), sumoylation (Mao et al, 2000) and ubiquitylation (Mao et al, 2001) that can alter the protein activity and localization.…”
Section: I25 E Coli Topoisomerase I Is Acetylatedmentioning
confidence: 99%
See 1 more Smart Citation